The Impact of Tourism Development on The Environment at AJ3 Playground - Afore Tahir Harefa; Ertaniat Lase; Ika Erwita Zebua (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The purpose of this research is to find out how the impact of tourism development on the environment. The research was conducted at one of the tourist attractions in Gunungsitoli, namely AJ3 Playground. AJ3 Playground is one of the recreational tourist attractions located in Afia village, North Gunungsitoli sub-district which is in great demand by people from both inside and outside Gunungsitoli. This research is qualitative. Using methods of collecting and evaluating data in context, qualitative research highlights certain social conditions through accurate descriptions of reality. The data collection techniques used were interviews, observations, field notes, and other forms of documentation used to gather information. Furthermore, data reduction, data presentation, and data verification/conclusion were conducted. The results showed that first, the development of tourism is good enough in terms of the 5 A aspects (attractions, activities, accessibility, accommodation, and amenities). Second, facilities and infrastructure have developed. Third, in its development, public awareness is still not optimal.